The Effect of Halal Certification and Veterinary Control Number (NKV) on The Purchase Intention of Beef Products in Depok City For Non-Muslim Consumers - Abdul Azis; Baga, Lukman M.; Asnawi, Yudha Heryawan (Indonesian Journal of Business and Entrepreneurship, 2024)
Starting in 2019 and 2020, the government began to make it mandatory to implement halal and NKV certification. The guarantee of food safety for beef products is not only halal certificates but also a Veterinary Control Number (NKV). Responds from non-Muslim consumers on the purchase intention of meat products with halal and NKV certificates are supporting factors in convincing sellers or producers to carry out the certification process. Therefore, this study aims to identify and analyze the influence of several factors, such as awareness, the role of certification, health reasons, and the parts of the halal marketing mix (product, price, promotion, and place). This research was conducted on 124 non-Muslim respondents selected by purposive sampling. Data were collected online and analyzed using PLS (Partial Least Square). The results show that awareness, the role of certification, health reasons, and the halal marketing mix (product, price, promotion, and place) affect the purchase intention of non-Muslims towards beef. There needs to be a role from various parties regarding information about halal and hygienic products. For example, sellers can inform consumers that the products they sell have been confirmed halal and the cleanliness of their products if an outbreak infects livestock at a certain time. Each group of respondents has differences in terms of factors influencing purchasing interest due to beliefs and habits. Keywords: beef, halal certification, food safety, purchase intention